Experimental study on the influence of patch load length on steel plate girders. (June 2020) - Kovacevic, S.; Markovic, N.
Abstract: An experimental study considering the behavior and ultimate strength of longitudinally unstiffened and stiffened I-steel plate girders reinforced by a single longitudinal stiffener subjected to patch loading is presented. The study represents an extension of the previous experimental investigation (Markovic and Kovacevic, 2019) [1] (N. Markovic, S. Kovacevic, Influence of patch load length on plate girders. Part I: Experimental research, J. Constr. Steel Res. 157 (2019), 207–228) in which we considered a different girder width. The main objective of this study is to elucidate and systematically investigate the influence of patch load length and web panel aspect ratio (changing the girder width) on the ultimate strength and behavior of longitudinally unstiffened and stiffened I-steel plate girders. The experimentally obtained patch load resistances are juxtaposed with ultimate loads available in the literature and determined by the design standard EN 1993-1-5. Patch load length and girder width have a significant influence on the ultimate strength of plate girders. The patch load resistance increases as the patch load length is increased, and this increase is more pronounced for longitudinally stiffened than for unstiffened girders. After a specific patch load length, the carrying capacity of longitudinally stiffened girders increases much faster with increasing patch load length. By using longer patch load lengths and longitudinal stiffeners, the ultimate strength can be significantly increased. Increasing the web panel aspect ratio leads to smaller ultimate loads and the effect of this ratio is more pronounced for longitudinally unstiffened girders. The patch load resistances of longitudinally unstiffened and stiffened girders determined by the design standard EN 1993-1-5 are smaller than the experimentally obtained ones, especially for stiffened girders and longer patch load lengths. Highlights: The patch load resistance of steel plate girders increases as the patch load length is increased. Longitudinal stiffener can significantly increase the patch load resistance of steel plate girders. An appreciable strengthening effect can be obtained when a specific patch load length is reached. Increasing the web panel width decreases the ultimate strength of steel plate girders. EN 1993-1-5 predicts lower ultimate strengths of steel plate girders, especially for longitudinally stiffened girders.